Characterizing highly cited papers in Social Work through H-Classics - Martínez Sánchez, María Ángeles; Herrera Gómez, Manuel; Jiménez Contreras, Evaristo; Ruiz, A.; Herrera-Viedma, Enrique (Scientometrics, 2017)
Highly cited papers are an important reference point in a research field. H-Classics is a new identification method of highly cited papers that is based on the H-index and is sensitive to the own characteristics of any research discipline and also its evolution. Recently, Ho (Scientometrics 98(1):137–155, 2014) presented a study on highly cited papers in Social Work area using as selection criterion a citation threshold value equal to 50 citations received. In this paper, we present a new study on the highly cited papers in Social Work discipline which is developed using the concept of H-Classics. This new study provides more precise results and a different vision on Social Work area.
Keywords: h-index; highly cited papers; bibliometric measures; social work; JCR; Scopus